Ethics and society in Nigeria : identity, history, political theory - Wariboko, Nimi, 1962- (Rochester : University of Rochester Press, 2019)
Offers a radical political interpretation of history that generates fresh insights into the emancipatory potential of ordinary Nigerians and their precolonial cultural institutions.
Introduction: Dead gods, divine kings, and deadly politicians -- The emergence of the lotus-self: personhood and identity -- Dead gods and people's revolts: political theory in religious acts -- The divine king and his five bodies: living history and the logic of interreligious dialogue -- Governance and deadly politicians: history as cultural criticism -- History without force: finding present space and place of time -- Constructing Nigeria's greatness: neglected paths of community, narratives, and care of the soul -- Mythos, virtues, and national transformation: the search for a standard of citizenship moral behavior -- African traditional religion and critical theory: a framework for social ethics.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed February 25, 2019).
JSTOR
Keywords: Social ethics -- Nigeria; Group identity -- Nigeria; Political corruption -- Nigeria; Nigeria -- Politics and government; Nigeria -- Religion; Identité collective -- Nigeria; Corruption (Politique) -- Nigeria; Nigeria -- Politique et gouvernement; PHILOSOPHY -- Ethics & Moral Philosophy; PHILOSOPHY -- Social; HISTORY -- Africa -- West; Group identity; Political corruption; Politics and government; Religion; Social ethics; Nigeria; Boston University; Democratic Republicanism; Emancipatory Politics; Ethics; Historical Identity; History; Human Flourishing; Identity; Moral Exemplars; Myth; Nigeria's Predicament; Nigeria; Nigerian Pentecostalism; Nimi Wariboko; Political Development; Political Philosophy; Political Theory; Precolonial Cultural Institutions; Religion; Societal Transformation; Society; Socio-Ethical Identity; Walter G. Muelder Professor of Social Ethics